The Importance of Metamemory Functioning to the Pathogenesis of Psychosis - Eisenacher, Sarah; Zink, Mathias (Frontiers in Psychology, 2017)
Many studies up to date have implied that biases in the metacognition of memory, so called metamemory, contribute to the development and maintenance of positive symptoms in schizophrenia. However, no study exists which has longitudinally followed patients experiencing positive symptoms. The present article therefore reviews cross-sectional studies on retrospective metamemory abilities in participants within different stages of a schizophrenia spectrum disorder, with heterogeneous symptom severities, creating a pseudo-longitudinal overview. Summarized, a deterioration of these abilities correlating with psychosis development can be inferred. The reviewed publications indicate that metamemory biases can already be found in patients with an at-risk mental state for psychosis (ARMS). Patients in their first episode of psychosis (FEP) seem to be more severely impaired than ARMS-patients but similarly affected compared to chronic patients. The contribution of these biases to the pathogenesis of psychosis is discussed, giving consideration to relations with other cognitive- and metacognitive functions, neurochemical processes and neural correlates. It is hypothesized that the biases represent early cognitive markers of the beginning and persisting psychotic state. An early treatment program could help patients to ameliorate the general course of illness or even to prevent the risk of a transition to psychosis.